Pediatric hematology and oncology fellow education in sexual and reproductive health: A survey of fellowship program directors in the United States. Issue 5 (8th March 2020) - Frederick, Natasha N.; Fine, Elizabeth; Michaud, Alexis; Recklitis, Christopher J.; Bober, Sharon L.
Abstract: Purpose: Pediatric oncology clinicians identify a need for increased sexual and reproductive health (SRH) education with adolescent and young adult (AYA) cancer patients. By surveying pediatric oncology fellowship directors, this study clarifies the state of current fellowship education about SRH for the AYA patient. Methods: A survey was sent to all pediatric oncology fellowship program directors (PDs) in the United States consisting of 13 questions pertaining to three primary SRH domains: sexual health, fertility, and safe sex practices. Descriptive statistics and χ 2 were used in data analyses. Results: Sixty‐three PDs responded to the survey (91% response rate). Of these, 88% reported having formal instruction regarding fertility, 41% reported curriculum regarding contraception and 30% reported some education regarding sexual health. The curriculum "being too full" was identified as a barrier to education on fertility (29%), sexual health (40%), and safe sex practices (38%). Not being a required or expected part of the program was more likely to be endorsed as a barrier for sexual health (26%) and safe sex practices (30%) compared with fertility (8%) ( P  < 0.005). Lack of experts to teach was a more frequently endorsed barrier to education on sexual health (47%) compared with either fertility (23%) or safe sex practices (25%) ( P  < 0.005). Conclusions: This study identifies important gaps in oncology fellow education about SRH. Future research must explore optimal education strategies that are feasible and acceptable by PDs and fellow learners, and effective in optimizing AYA SRH care.